Long-term survivors of cardiac arrest: A narrative inquiry. (August 2019) - Haydon, Gunilla; van der Riet, Pamela; Inder, Kerry
Background: Despite extensive knowledge and research in cardiac health there is limited understanding in how a cardiac arrest influences the life of long-term survivors. Objective: The aim of this study was to explore how long-term survivors of a cardiac arrest adjusted to their new reality, expressed in their re-storied narratives. Methods: Seven individuals surviving a cardiac arrest 5–26 years ago were interviewed through in-depth conversations over a six-month period. These interviews were analysed using Clandinin and Connelly's framework of narrative inquiry. Results: Seven threads were found: Disbelief, Surveillance of their body, Loss of control and desire for normality, Keeping fit and informing others, Gratefulness, Spirituality – luck and fate, and Fragility of life and dying. Conclusions: All seven long-term survivors of cardiac arrest expressed a positive attitude. Despite the nature of the cardiac arrest and the hurdles that followed, they have a heightened appreciation for life. This indicates that after the adaptation to their new reality of being a cardiac arrest survivor life returns to a new normality.